Improving quality of rice straw through treatment with urea and midden soil for large animals (Bangladesh Journal of Animal Science, 2013)
Twelve indigenous growing cattle (live weight 130.00 ± 1.67 kg) were selected and divided into four groups having three animals in each group. Group A, B, C and D supplied 3.0% urea + 2.0% midden soil, 3.0% urea + 3.0% midden soil, 3.0% urea + 4.0% midden soil and 3.0% urea + 5.0% midden soil treated rice straw. In addition to this all the animals were supplied 2 Kg green grass, 450 g concentrate mixture and 40 g salt per 100 kg body weight. Rice straw treated with 3.0% urea+ 2.0% midden soil resulted an improvement in crude protein content of rice straw from 3.30 to 7.08% which was further increased by 7.40, 7.90 and 8.14% treatment with 3.0% urea + 3.0% midden soil, 3.0% urea + 4.0% midden soil and 3.0% urea + 5.0% midden soil respectively. The addition of 5.0% midden soil as a urease source with 3.0% urea (D) treated rice straw not only significantly (P